PENGARUH KUALITAS PRODUK,CITRA MEREK DAN PEMASARAN ONLINE TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada PT. Havindo Pakan Optima) - Nugroho, Iskan Aryo; Dirgantara, I Made Bayu (Faculty of Economics and Business Diponegoro University, 2021)
This study aims to examine the effect of product quality, brand image and online marketing on purchasing decisions. The independent variables used in this study are product quality, brand image and online marketing. The dependent variable in this study is the purchase decision.This study uses primary data. The population of this research is the consumers of PT. Havindo Feed Optima. The research sample was selected by purposive sampling method and obtained a sample of 100 respondents who met the criteria. Test analysis using multiple regression analysis model.The results showed that the product quality variable had a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions. Online marketing has a positive and significant effect on purchasing decisions